2023
DOI: 10.1002/ajb2.16202
|View full text |Cite
|
Sign up to set email alerts
|

Herbs are not just small plants: What biomass allocation to rhizomes tells us about differences between trees and herbs

Abstract: Premise: Biomass accumulation over years in vertical stems of trees leads to hypoallometric scaling between stem and leaf biomass within this growth form, while for herbaceous species, biomass allocation between these organ types typically exhibits isometry. However, biomass accumulation in herbs can occur in belowground perennating organs (e.g., rhizomes) that are, contrary to aboveground parts of herbs, long-lived. Although ecologically important, biomass allocation and accumulation in rhizomes (and similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Productivity implies the role of BGFs in the carbon economy of plants. It has recently been shown that clonal growth organs can contain a large proportion of total plant carbon (Harris et al ., 2023) and that their building represents a significant carbon sink, namely for young plants (Martínková et al ., 2020). The presented results support these findings on a much larger set of species and habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Productivity implies the role of BGFs in the carbon economy of plants. It has recently been shown that clonal growth organs can contain a large proportion of total plant carbon (Harris et al ., 2023) and that their building represents a significant carbon sink, namely for young plants (Martínková et al ., 2020). The presented results support these findings on a much larger set of species and habitats.…”
Section: Discussionmentioning
confidence: 99%
“…While coarse roots are ubiquitous, clonal organs such as rhizomes or bulbs are especially common in herbs and shrubs, and may constitute a large part of their overall biomass. For example, belowground rhizomes may form 30% of herb total biomass because they are perennial and thus can accumulate over years, in contrast to aboveground herbaceous plant parts (Harris et al ., 2023). These organs and their belowground position must have some important function in plant life because plants have various adaptations to place them belowground or to position them horizontally at the soil surface.…”
Section: Introductionmentioning
confidence: 99%